Validation of an online version of the trier social stress test in adult men and women. (August 2022) - Meier, Maria; Haub, Kristina; Schramm, Marie-Luise; Hamma, Marc; Bentele, Ulrike U.; Dimitroff, Stephanie J.; Gärtner, Raphaela; Denk, Bernadette F.; Benz, Annika B.E.; Unternaehrer, Eva; Pruessner, Jens C.
Abstract: The Trier Social Stress Test (TSST) is a reliable and efficient protocol to induce acute psychosocial stress in the laboratory. If circumstances do not allow in-person assessments, an online version of the TSST could create more flexible research opportunities. To date, studies have confirmed subjective and autonomic stress responses to online TSST protocols. In this preregistered study (https://osf.io/u57aj ), we focused on the effect of a TSST online for adults (TSST-OA) on cortisol and alpha amylase levels, and pleasure and arousal ratings. As cortisol stress reactivity is mediated by sex, we further compared men and women. We hypothesized significant increases in cortisol, alpha amylase and arousal, and a decrease in pleasure in response to the TSST-OA. Also, we expected stronger cortisol responses in males as compared with females, as in the laboratory TSST. N  = 48 adults (56% female, meanage =23.02 years, SD=3.19) participated in the study. Saliva sampling devices were sent to participants' home before testing sessions, during which the experimenter, a mixed-sex panel, and the participant joined a video call. Participants underwent the TSST-OA and overall provided five saliva samples for cortisol and alpha amylase detection. Pleasure and arousal ratings and psychometric questionnaires were also completed online. As hypothesized, the TSST-OA significantly increased cortisol, alpha amylase, and arousal levels, while it decreased pleasure. Moreover, cortisol responses were significantly stronger in males as compared to females. 64% of subjects were classified as responders (cortisol rise>1.5nmol/l). The TSST-OA successfully induced psychophysiological stress in adults. Our protocol offers new possibilities to study stress outside of the laboratory. Highlights: The Trier Social Stress Test (TSST) is a reliable standardized protocol to induce acute psychosocial stress in the laboratory. We administered an online, adult-version of the TSST (TSST-OA) via videocall in healthy men and women. The TSST-OA increased cortisol, alpha amylase levels as well as subjective arousal, while it decreased subjective pleasure. The cortisol response to the TSST-OA was stronger in men as compared with women.